Hydrological Systems in the Greater Virunga Landscape: Water Quality around Mikeno Sector - Karume, Katcho; Bagalwa, Mashimango; Yalire, Mapendano; Kazi, Katya; Mukengere Bagula, Espoir; Bitariho, Robert; Nahayo, Deogratias; Kasangaki, Aventino; Byamukama, James (Journal of Water Resource and Protection, 2016)
Monitoring of environmental parameters is one of the highest priorities in the evaluation of environmental status of water resources and in environmental protection policy. The main objectives are to understand and evaluate the water quantity and quality in order to provide water of appropriate quality to various water users. The water quantity was assessed by the measurement of runoff or discharge at specific river cross sections using floating method for surface water and bucket and stopwatch method for springs and boreholes. The quality of river water and spring was identified in terms of its physical, chemical, and biological parameters. The analyzed data were compared with standard values recommended by WHO. Macroinvertebrates were collected in the rivers using a plankton nets and 10 minutes of sampling. Identification was made at the laboratory of Malacology. Results revealed that the quality of water obtained from sampling points is generally good to use for different domestic purposes except the Idanta River and Rwembwe borehole, which need an appropriate treatment before use. All sampling points are located far from houses and latrines, which can contribute to fecal contamination. On the different sampling points, bathing and washing clothes were observed and could constitute the source of pollution of drinking water. In Idanta and Kamira Rivers animals used water for drinking while also people use this water for domestic and drinking. In the two sampling points high values of Escherichia coli
Keywords: environmental parameters; water resources; environmental protection policy